Individual Assembly of Radical Molecules on Superconductors: Demonstrating Quantum Spin Behavior and Bistable Charge Rearrangement - Li, Chao; Pokorný, Vladislav; Žonda, Martin; Liu, Jung-Ching; Zhou, Ping; Chahib, Outhmane; Glatzel, Thilo; Häner, Robert; Decurtins, Silvio; Liu, Shi-Xia; Pawlak, Rémy; Meyer, Ernst (ACS nano, 2025)
High-precision molecular manipulation techniques are used to control the distance between radical molecules on superconductors. Our results show that the molecules can host single electrons with a spin 1/2. By changing the distance between tip and sample, a quantum phase transition from the singlet to doublet ground state can be induced. Due to local screening and charge redistribution, we observe either charged or neutral molecules, which couple in a sophisticated way, showing quantum spin behavior that deviates from the classical spins. Dimers at different separations show multiple Yu-Shiba-Rusinov peaks in tunneling spectroscopy of varying intensity, which are in line with the superconducting two-impurity Anderson model, where singlet (S = 0) and doublet (S = 1/2) ground states are found. The assembly of chains of 3, 4, and 5 molecules shows alternating charge patterns, where the edge molecules always host a charge/spin. The tetramer is observed in two configurations, where the neutral site is moved by one position. We show that these two configurations can be switched by the action of the probing tip in a nondestructive manner, demonstrating that the tetramer is an information unit, based on single-electron charge reorganization.
Keywords: superconductors; molecular manipulation; radical molecules; Yu-Shiba-Rusinov states; spin switch; scanning tunneling microscopy